Check on the features of potted 20-inch PMTs with 1F3 electronics prototype at Pan-Asia. (1st February 2023) - Liu, Caimei; Li, Min; Wang, Zhimin; Hu, Jun; Anfimov, Nikolay; Fan, Lei; Garfagnini, Alberto; Gong, Guanghua; Hou, Shaojing; Ji, Xiaolu; Jiang, Xiaoshan; Korablev, Denis; et al.
Abstract: The Jiangmen underground neutrino observatory (JUNO) is a neutrino project with a 20-kton liquid scintillator detector located 700-m underground. The large 20-inch PMTs are one of the crucial components of the JUNO experiment aiming for precision neutrino measurements with better than 3% energy resolution at 1 MeV. The excellent energy resolution and a large fiducial volume provide many exciting opportunities for addressing important topics in neutrino and astroparticle physics. With the container #D at JUNO Pan-Asia PMT testing and potting station, the features of waterproof potted 20-inch PMTs were measured with JUNO 1F3 electronics prototype in waveform and charge, which are valuable for a better understanding of the performance of the waterproof potted PMTs and the JUNO 1F3 electronics. In this paper, the basic features of the JUNO 1F3 electronics prototype run at Pan-Asia will be introduced, followed by an analysis of the waterproof potted 20-inch PMTs and a comparison with the results from commercial electronics used by container #A and #B.